Evaluating the COVID−19 impact on tourism and access routes to Spain: A counterfactual analysis - Aida Galiano Martínez; Juan Manuel Martín-Alvarez; Miguel Angel Del Arco Osuna; Lara Mata Martínez (Annals of Tourism Research Empirical Insights)
This research examines the impact of COVID-19 on Spanish international tourism, focusing on the routes of access to the country. Using data from October 2015 to March 2024, a counterfactual analysis was conducted to calculate the severity of the impact on Foreign Tourism Access to Spain by Air Transport, Road, Railway, and Maritime Transport. Benchmark series were calculated using the SARIMA model and validated with Machine Learning methods. Results show significant increases in Air and Road access post-pandemic, with even larger increases in Railway and Maritime routes, indicating early recovery trends since May 2023. These findings highlight the need for adaptive marketing strategies to align with new travel preferences for sustainable and health-conscious travel options.